Non-mercury catalytic acetylene hydrochlorination over Ru catalysts enhanced by carbon nanotubes1. Issue 12 (11th February 2015) - Li, Guangbi; Li, Wei; Zhang, Haiyang; Pu, Yanfeng; Sun, Mengxia; Zhang, Jinli
<x xml:space="preserve">Abstract</x> Ru catalysts deposited inside the channels of the CNTs show higher catalytic activity. Ru-in-CNT catalyst exhibited an acetylene conversion of 95.0% at 170 °C and 10 h. CNTs with an inner diameter of 3–7 nm can functionalize as an efficient support.